A Phase IIa Study Evaluating Safety, Pharmacokinetics, and Antiviral Activity of GSK2838232, a Novel, Second-generation Maturation Inhibitor, in Participants With Human Immunodeficiency Virus Type 1 Infection. (26th November 2019) - DeJesus, Edwin; Harward, Sara; Jewell, Roxanne C; Johnson, Mark; Dumont, Etienne; Wilches, Viviana; Halliday, Fiona; Talarico, Christine L; Jeffrey, Jerry; Gan, Jianjun; Xu, Jianfeng; Felizarta, Franco; et al.
Abstract: Background: GSK2838232 is a second-generation, potent, small-molecule, oral human immunodeficiency virus type 1 (HIV-1) maturation inhibitor for once-daily administration boosted with a pharmacoenhancer. Methods: The phase 2a, proof-of-concept study was an open-label, adaptive dose-ranging design. Safety, pharmacokinetics, and efficacy of GSK2838232 boosted by cobicistat were evaluated in individuals with HIV-1 infection. The study participants (N = 33) received GSK2838232 once daily across a range of doses (20–200 mg) with cobicistat 150 mg for 10 days. Results: GSK2838232 was safe and well tolerated with no clinically meaningful changes in safety parameters or adverse events. Exposure (maximum concentration and area under the concentration-time curve from time zero to the concentration at 24 hours postdose) increased 2- to 3-fold with repeated dosing in an approximately dose-proportional manner, reaching steady-state by day 8 with a half-life (t½) from 16.3 to 19.2 hours. Clearance and t½ values were not dependent on dose. Viral load declined from baseline with all GSK2838232 doses. Mean maximum declines from baseline to day 11 in HIV-1 RNA log10 copies/mL with the 20-mg, 50-mg, 100-mg, and 200-mg cohorts were −0.67, −1.56, −1.32, and −1.70, respectively. CD4 + cell counts increased at doses ≥50 mg. Conclusions: GSK2838232 with cobicistat was well tolerated and exhibited efficacy as a short-term monotherapy in participants with HIV-1. This positive proof-of-concept study supports the continued development of GSK2838232 for the treatment of HIV as part of combination antiretroviral therapy. Clinical Trials Registration: NCT03045861. Abstract : A new oral HIV-1 maturation inhibitor, GSK2838232, when administered as capsules with cobicistat for 10 days, was well tolerated and exhibited antiviral efficacy in participants with HIV-1.